KEGIATAN IMPULSE BUYING PADA GEN Y DI KABUPATEN SUMEDANG - Ria Arifianti; Farah Putri Firsanty (POLITEKNIK LP3I JAKARTA, 2025)
The phenomenon of shopping is an interesting discussion reviewed from a social and economic perspective, the development of the era gives rise to perceptions and purposes of shopping. One of them is impulse buying. This article aims to explain how impulse buying is done by Gen Y. This writing also aims to describe examples and concrete forms of Generation Y shopping behavior. This study uses the theory of Rook and Fisher (2007) which states that spontaneous buying (Impulse Buying) is a purchasing decision made by customers or consumers that is done spontaneously or immediately after seeing the merchandise offered. This means that spontaneous buying is an activity that is carried out unplanned to make a previous purchase. Purchases in impulse buying are not based on needs but purchases made based on interest in an item. Emotional considerations are dominant in this type. This behavior is uncontrolled behavior (out-of-control). The method used is descriptive. The descriptive research conducted aims to create a systematic, factual, and accurate description or picture of impulse buying in Generation Y. Based on the results of the analysis, it was found that spontaneous, reflexive, sudden, and automatic decisions occurred in shopping activities. There are factors and impacts caused by impulse buying on generation Y in Sumedang Regency.